The Influence of ROA, DER, and Tax Planning on Corporate Income Tax Payable (A Study on Mining Companies Listed on the Indonesia Stock Exchange for the Period 2017 - 2021) - Kristina, Lahana; Chairunnisa, Mariyam (Jurnal Ilmu Ekonomi dan Sosial (JIES), 2024)
This research aims to investigate the influence of ROA, DER, and tax planning on corporate income tax payable in mining companies listed on the Indonesia Stock Exchange during the period 2017-2021. The research method used is a quantitative causal study. This approach is based on positivism philosophy and aims to test predetermined hypotheses. The population of this study consists of 45 mining companies listed on the Indonesia Stock Exchange during the specified period. The sampling technique used is non-probability sampling, employing purposive sampling to select samples. The total sample used in this study is 11 companies. The research results indicate that ROA, DER, and tax planning have a significant influence on corporate income tax payable. This research uses the EViews version 10 software measuring tool.